S88 Mast cell myositis is associated with persistent airflow limitation (PAL) in childhood severe asthma (SA). (16th November 2010) - Bossley, C J; Oates, T; Regamey, N; Fleming, L; Lloyd, C; Bush, A; Saglani, S
Abstract : Background: Studies of airway inflammation and remodelling may help us to understand the pathophysiology of SA. Adult studies have shown mast cell inflammation within smooth muscle is specific to asthma and is associated with airway hyperresponsiveness (AHR). However, this has not been studied in childhood disease. Hypothesis: Children with SA have increased submucosal eosinophils and mast cells within smooth muscle compared to age-matched mild asthmatics and non-asthmatic controls. Methods: 75 children, mean age 11.8 (5.6–17.3) years, 53 with SA, 7 with mild/moderate asthma (MA) and 15 non-asthmatic controls (bronchoscoped for upper airway symptoms) were included. All underwent spirometry and bronchodilator reversibility, fractional exhaled nitric oxide (FeNO) measurement, fibreoptic bronchoscopy with bronchoalveolar lavage (BAL) and endobronchial biopsy (EB). EB were stained for: eosinophils (congo red), neutrophils (neutrophil elastase), mast cells (mast cell tryptase); and reticular basement membrane (RBM) thickness, epithelial shedding and volume fraction (Vv) of smooth muscle. Results: See Abstract S88 Table 1 . Children with SA had significantly increased BAL and submucosal eosinophils compared to controls. There were no significant group differences in submucosal mast cells, but the presence of mast cells within smooth muscle exhibited a non-significant trend to be increased in SA and MA. Children with mast cells within smooth muscle were more likely to have PAL (post bronchodilator, post steroid trial FEV1 <80% predicted) (p<0.05). The Vv of subepithelial tissue occupied by airway smooth muscle (ASM) was only increased in SA. Conclusions: Children with SA have increased luminal and submucosal eosinophilia. However, in contrast to reports in adults of AHR being associated with mast cell myositis, we have found severe asthmatic children with mast cell myositis were more likely to have PAL. Mast cell myositis may be a feature of severe asthma in children.